#ILookLikeASurgeon: embracing diversity to improve patient outcomes. (10th October 2017) - Logghe, Heather; Jones, Christian; McCoubrey, Alison; Fitzgerald, Edward
Abstract : The stereotype of the arrogant, white, male surgeon is a barrier to professionals